HADIS DALAM PANDANGAN JAMA'AH TABLIGH - Hakim, Lukman (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2022)
This study aims to obtain information about the Perception of Jamaa'ah Tabligh in understanding the Hadith of the Prophet, which is related to the hadith about their way of dressing, namely white robes, turbans and trousers above the ankles, or Cingkrang trousers. Likewise with the Khuruj da'wah activities, namely leaving the hometown for a period of 3 days to 40 days. The religious activities carried out are expected to help improve the values ​​of Islamic religious education. This type of research is entirely library research taking data from literature that is related to the research theme. The analysis technique in this writing uses a content analysis model by exploring and analyzing the thoughts or views of Jama'ah Tabligh on the Hadiths of the Prophet that they practice in everyday life.